The use of alteplase, although safe, does not offer clear clinical advantages when mild stroke is non-disabling - Merlino, Giovanni; Nesi, Lorenzo; Vergobbi, Pietro; Scanni, Marco Domenico; Pez, Sara; Marziali, Alessandro; Tereshko, Yan; Sportelli, Giuseppe; Lorenzut, Simone; Janes, Francesco; Gigli, Gian Luigi; Valente, Mariarosaria (Frontiers in Neurology, 2023)
It is unknown if alteplase is effective and safe in patients with mild acute ischemic stroke (AIS). Determining whether symptoms are "disabling" or not is the crucial factor in the management of these patients. The aim of this study was to investigate the efficacy and safety of alteplase in subjects with mild, non-disabling AIS.We included all consecutive patients admitted at our institution from January 2015 to May 2022 for AIS with a baseline NIHSS score of 0-5 and suitable for intravenous thrombolysis. In order to select only subjects with non-disabling AIS, we excluded patients who scored more than 1 point in the following NIHSS single item: vision, language, neglect and single limb. Patients who scored at least 1 point in the NIHSS consciousness item were excluded as well. This study is a retrospective analysis of a prospectively collected database. After application of the excluding criteria, we included 319 patients, stratified into patients receiving and not receiving alteplase just because of non-disabling symptoms. The two groups were comparable regarding demographic and clinical data. Rates of three-month favorable outcome, defined as three-month mRS score 0-1, were similar, being 82.3% and 86.1% in treated and untreated patients, respectively. Hemorrhagic complications and mortality occurred infrequently and were not affected by alteplase treatment. This observational study suggests that the use of alteplase, although safe, is not associated with a better outcome in highly selected patients with non-disabling AIS.